Implementasi Matriks Skew-symmetric dalam Metode Kriptografi Affine-Hill Cipher - Putri Nisa Pratiwi; Sisilia Sylviani (Mathematical Sciences and Applications Journal, 2023)
The concept of cryptography is widely used to reduce data security threats along with developments in information technology. Affine Cipher is an example of classic cryptography that utilizes modular operations and shifts on characters. On the other hand, Hill Cipher method is more dependent on matrix operations. The combination of the two methods, Affine-Hill Cipher, creates a more complex and superior method in terms of security. In this research, we utilize a square skew-symmetric matrix with an order corresponds to the secret key to construct the key matrix. The encryption and decryption processes are carried out using the Affine-Hill Cipher and adding the key exchange concept into the algorithm. The results indicate that this algorithm’s complexity can effectively reduce data security threats.